The late Henry Moss ; Eyes for Consuela ; When the world was green : three plays - Shepard, Sam, 1943-2017 (2002)
"These three plays by Sam Shepard are bold, explosive, and ultimately redemptive dramas propelled by family secrets and illuminated by a searching intelligence. In The Late Henry Moss - which premiered in San Francisco, starring Sean Penn and Nick Nolte - two estranged brothers confront the past as they piece together the drunken fishing expedition that preceded their father's death. In Eyes for Consuela, based on Octavio Paz's classic story "The Blue Bouquet," a vacationing American encounters a knife-toting Mexican bandit on a gruesome quest. And in When the World Was Green, cowritten with Joseph Chaikin, a journalist in search of her father interviews an old man who resolved a generations-old vendetta by murdering the wrong man. Together, these plays form a powerful trio from an enduring force in American theater"--Page 4 of cover
The late Henry Moss -- Eyes for Consuela -- When the world was green
"A Vintage Books original."
Keywords: American drama -- 20th century